Nevirapine Pharmacokinetics in Neonates Between 25 and 32 Weeks Gestational Age for the Prevention of Mother-to-Child Transmission of HIV. Issue 4 (8th March 2021) - Hirt, Déborah; Kubota Kilengelela, Jean; Jarreau, Pierre-Henri; Tréluyer, Jean-Marc; Marcou, Valérie
Abstract : Supplemental Digital Content is available in the text. Abstract : Eleven newborns from 25 to 32 weeks of gestational age, weighting from 0.66 to 1.60 kg received 2 mg/kg doses of nevirapine syrup. In 15 samples, collected 8.75–89 hours after drug intake, concentrations ranged from 0.65 to 16.68 mg/L. Three nevirapine dose of 2 mg/kg at day 0, 2 and 6 days of life achieved nevirapine concentrations above the proposed nevirapine target for HIV prophylaxis for at least 11 days.